Pelaporan Kewangan Menerusi Internet: Indeks, Tahap Pelaporan dan Faktor Penentunya - Mohd Noor Azli, Ali Khan (2010)
The purpose of this study is to investigate the relationship between Internet Financial Reporting (IFR) with contingency factors and firm specific characteristics. IFR is represented by dimension of content, dimension of presentation and overall index of IFR. This study is motivated by the inconsistent findings concerning dimensions used to represent IFR as appeared in the contemporary literature. Due to the inconsistencies in the findings, a new research stream emerged. The research stream suggests future researchers to investigate in more detail variables that can clarify the determinants of IFR practices. Therefore, this study integrates the IFR literature, contingency literature and financial reporting literature through the investigation of the contingency factors and firm specific characteristics. Contingency factors have been widely discussed in management accounting literature as important variables for the purpose of strategy implementation. In this study, two contingency factors and ten firm specific characteristics had been identified from the financial disclosure literature. Firm specific characteristics were measured by using three main variables, namely:structure, performance and market. This study obtained responses from the preparers of annual reports in relation with the items that should be included in the checklist of IFR index.Random sampling was used in selecting the sample of the study with the characteristics of the Malaysian preparers accordingly. Out of 450 questionnaires distributed, 68 questionnaires(15.11%) were returned and used for further analysis. The response rate was considered sufficient as it was paralleled with responses from previous studies. In addition, data was collected from 182 companies listed in the main board of Bursa Malaysia for the purpose of multiple regression analysis. This study found that 87 out of 155 items were identified as a basic measurement to determine the level of IFR among the listed companies in main board of Bursa Malaysia. The study found that a mean score of IFR is 65.10 with the highest score of 78.16 and the lowest score of 48.27. Based on multiple regressions analysis, the findings showed that three main firm specific characteristics influenced the level of IFR i.e. firm size,listing period and return on equity. The findings also showed that there was a negative relationship between profitability ratio and dimension of content and overall index of IFR.This study provides important implication for accounting standard setters, regulators and authority bodies in developing a guideline for practicing disseminate financial information through company websites. These findings should be of interest to other researchers, and to managers and investors who currently use or plan to use financial information in making rational investment decisions. In conclusion, findings from this study have contributed to the enhancement of the understanding on the subject matter and more importantly it also contributes to the development and affirmation of theories in the field of IFR.